Evaluating zeolite stability as a mycotoxin binder in broiler chickens’ growth performance: A meta-analysis - Tri Ujilestari; Danung N. Adli; Mochamad D. Alifian; Agung Irawan; Rizki A. Nurfitriani; Mohammad F. Hudaya; Amirul F. Azmi; Sugiharto Sugiharto; Mohammad M. Sholikin (Iraqi Journal of Veterinary Sciences, 2025)
Mycotoxin contamination in broiler chicken feed negatively impacts health, growth, and feed efficiency. This study aimed to assess the efficacy of zeolite additives in enhancing growth performance and reducing mortality in broiler chickens exposed to mycotoxins. A systematic review was conducted, analysing relevant studies published between 1970 and 2025, sourced from databases such as BASE, JSTOR, PubMed, ScienceDirect, and Scopus. Of the 169 identified articles, 13 met the inclusion criteria, covering 70 experiments. Publication bias was evaluated using Egger’s test, and a random-effects model Hedges (g’) was applied to calculate effect sizes. Zeolite supplementation significantly improved average daily gain (ADG), daily feed intake (DFI), and feed conversion ratio (FCR) in mycotoxin-exposed broiler chickens, with effect sizes consistently exceeding g’ > 0.8 (P<0.01). Aflatoxin, aflatoxin B1, and ochratoxin A exhibited the highest responsiveness to zeolite. Improvements were observed across all rearing phases, particularly during the starter and finisher stages. Clinoptilolite-based zeolite significantly reduced FCR and mortality rates (g’ > |0.8|, P<0.05); however, overall mortality rates remained largely unchanged. These findings indicate that zeolite supplementation, particularly clinoptilolite, represents a viable dietary strategy for mitigating mycotoxin exposure in poultry production systems by enhancing growth performance and alleviating mycotoxin-related adverse effects.